2020
DOI: 10.1136/annrheumdis-2020-216972
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis in the oral microbiomes of anti-CCP positive individuals at risk of developing rheumatoid arthritis

Abstract: ObjectivesAn increased prevalence of periodontitis and perturbation of the oral microbiome has been identified in patients with rheumatoid arthritis (RA). The periodontal pathogen Porphyromonas gingivalis may cause local citrullination of proteins, potentially triggering anti-citrullinated protein antibody production. However, it is not known if oral dysbiosis precedes the onset of clinical arthritis. This study comprehensively characterised the oral microbiome in anti-cyclic citrullinated peptide (anti-CCP) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 44 publications
7
82
0
1
Order By: Relevance
“…In general, enrichments of periodontitis-associated species, such as in Prevotella , Alloprevotella , Fusobacterium and Filifactor were reported in patients with established RA [ 19 , 43 , 44 ]. A few studies, mainly recent ones, have targeted early-stage RA and patients with ACPA positive arthralgia but no sign of arthritis, i.e., patients at risk for RA [ 6 , 9 , 18 , 21 ]. Some report that periodontal signs are more severe already at early RA/at-risk-stages [ 6 , 18 ], but this was not confirmed in recent Dutch [ 21 ] or, though there was a tendency, in the present Swedish population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, enrichments of periodontitis-associated species, such as in Prevotella , Alloprevotella , Fusobacterium and Filifactor were reported in patients with established RA [ 19 , 43 , 44 ]. A few studies, mainly recent ones, have targeted early-stage RA and patients with ACPA positive arthralgia but no sign of arthritis, i.e., patients at risk for RA [ 6 , 9 , 18 , 21 ]. Some report that periodontal signs are more severe already at early RA/at-risk-stages [ 6 , 18 ], but this was not confirmed in recent Dutch [ 21 ] or, though there was a tendency, in the present Swedish population.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of P. gingivalis and Aa remains unclear in RA development. Thus, some studies using 16S ribosomal RNA (16S rRNA) high-throughput sequencing find a higher abundance of P. gingivalis and/or Aa in early and established RA as well as in patients at risk for RA (ACPA positive arthralgia) [ 6 , 9 , 18 ], whereas others do not [ 19 , 20 , 21 , 22 ]. Anyhow, several of the studies emphasize the importance of characterizing the entire microbiota, map to the species level, and distinguishing between periodontally healthy and diseased states and treatment immune modifying anti-rheumatic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Besides genetic factors, P. gingivalis represents one of the main environmental factors that can lead to autoimmune arthritis, which can induce citrullinated peptides. Citrullinated peptides are a source of anticitrullinated antibodies (ACPAs), which can predict the occurrence and the future development of RA [ 14 ]. An increasing number of studies have found a correlation between P. gingivalis infection and ACPA-positive RA [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mikuls et al described that anti-P. gingivalis concentrations have been significantly associated with autoantibody-positive and high-risk status of developing RA (130). There is a characteristic alteration in the composition of salivary microbes in individuals at high-risk for RA, suggesting that oral microbiota dysbiosis occurs in the "pre-clinical" stage of RA (131)(132)(133). Moreover, among patients with RA, PD severity appears to independently predict RA severity (134,135).…”
Section: Periodontal Diseasementioning
confidence: 99%